Association of Small Intestinal Bacterial Overgrowth With Heart Failure and Its Prediction for Short‐Term Outcomes - Song, Yu; Liu, Yuan; Qi, Baozhen; Cui, Xiaotong; Dong, Xinyue; Wang, Yanyan; Han, Xueting; Li, Fuhai; Shen, Dongli; Zhang, Xian; Hu, Kai; Chen, Shiyao; et al. (Journal of the American Heart Association, 2021)
Background Small intestinal bacterial overgrowth (SIBO) is a common pathological condition of intestinal microbiota. The prevalence of SIBO and its prognostic value in patients with heart failure (HF) are unknown. Methods and Results A total of 287 patients tested for SIBO using lactulose hydrogen-methane breath test were evaluated. At least 1 of the following criteria fulfilled was SIBO positive: patients with fasting hydrogen level ≥20 parts per million (ppm) or a ≥20 ppm rise in hydrogen by 90 minutes were diagnosed with SIBO (H ) positive; and patients with methane levels ≥10 ppm at any test point were diagnosed with SIBO (CH ) positive. The association between SIBO and the composite of cardiovascular death and HF rehospitalization was investigated. In 287 consecutive patients with HF, 128 (45%) were positive for SIBO. Our result showed SIBO increased the risk of HF rehospitalization in patients with HF with reduced ejection fraction ( <0.001), and the risk of cardiovascular death in patients with HF with preserved EF ( =0.011). SIBO was an independent risk factor of primary end point in patients with HF (hazard ratio [HR], 2.13; 95% CI; 1.26-3.58; =0.005). In addition, SIBO (CH ) showed a prognostic value on adverse outcomes (HR, 2.35; 95% CI, 1.38-4.02; <0.001), whereas the association between SIBO (H ) and outcomes was not statistically significant. Conclusions There was high prevalence of SIBO in patients with HF, and SIBO was independently associated with poor outcomes. Proactive treatment for SIBO may provide extra benefit for patients with HF.